PENGARUH DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DI HOTEL GRAND ROCKY BUKITTINGGI - Tanjung, Nora Cetisia; Waryono, Waryono; Abrian, Youmil (Journal of Home Economics and Tourism, 2017)
This study aims to determine the influence between work discipline on employee performance at Grand Rocky Hotel Bukittinggi. The type of this research is clausal assosiative. The sampling technique is using proportional random sampling. The sample of this research are amounted to 51 people. Data collection is using questionnaire. The primary’s data is work discipline and the secondary’s data is employee performance. Based on likert scale that has been tested of validity and reliability. The result of this research is concluded that in general about work discipline at Grand Rocky Hotel Bukittinggi is good at 47,06%. Employee performance at Grand Rocky Hotel Bukittinggi is also good at 50, 98%. The result is also indicate that signification between work discipline on employee performance at Grand Rocky Hotel Bukittinggi is 81,8%.Key Word: Discipline, Performance, Employee